CHARACTERIZATION OF ETHYL ACETATE-BASED LEAF EXTRACT OF Entada rheedii Spreng. BY USING LIQUID CHROMATOGRAPHY QUADRUPOLE TIME-OF-FLIGHT MASS SPECTROMETRY (Applied Biological Research, 2025)
Plants possess diverse characteristics and medicinal properties, and since antiquity, various parts such as leaves, stems, roots, rhizomes, flowers, tendrils, and bulbs have been utilized in the preparation of therapeutic products. Entada rheedii Spreng., a species native to tropical regions, has traditionally been used to treat a range of ailments. The present study aimed to characterize the major chemical constituents of E. rheedii leaf extract using liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (LC-MS-QTOF). This analytical technique facilitated the identification of several bioactive flavonoids, including apigenin, genistein, kaempferol, nicoflorin, astragalin, quercetin, and spiraeoside. LC-MS-QTOF analysis revealed distinct peaks corresponding to these compounds, with retention times of 4.79 and 8.58 minutes. Structural confirmation was achieved through consistent fragmentation patterns. These flavonoids are known for their significant pharmacological activities, including antioxidant, anti-inflammatory, and anticancer effects. The findings provide valuable insights into the phytochemical profile of E. rheedii leaves, supporting their potential medicinal applications.
Keywords: Entada rheedii; ethyl acetate extract; plant secondary metabolites; characterization; bioactivity analysis